Marketing Performance and Family-Owned Successor Skills in Foreign-Owned Businesses in Cambodia - Chea, Mengtieng; Try, Chanthuch; Sou, Veasna (International Journal of Indonesian Business Review, 2025)
Purpose – Cambodia's liberal investment policies and economic growth have led to an increase in foreign-owned enterprises (FOEs), which often incorporate family-owned local partners. Market conditions, firm resources, and successor skills influence marketing performance in these hybrid business arrangements. This study investigates the relationship between family-owned successor skills and marketing performance in Cambodian FOEs, identifying critical successor competencies for success and offering managerial implications. Methodology/Approach – The study employed purposive sampling to gather information from foreigners with family businesses in Phnom Penh, Ta Khmau, and Sihanoukville, Cambodia. With 420 questionnaires distributed, 328 returned, and 38 rejected, 290 respondents provided valid data, aligning with Bowerman et al.'s formula for quantitative research and structural equation modelling (SEM). Findings – The study reveals that experiential knowledge and environmental sustainability intention significantly predict business alignment, positively influencing marketing performance and successor skills. The model supports hypotheses and offers valuable insights for strategic and succession planning, despite the rejection of the hypothesis about the family business mindset. Novelty/value – The study explores the impact of family-owned successor skills on marketing performance in foreign-owned businesses in Cambodia, using succession theory, marketing capability frameworks, resource-based view, knowledge-based View, stewardship theory, strategic fit theory, dynamic capabilities theory, and experiential learning theory to explain the research hypothesis development as proposed in Figure 1.